Patriarki Dalam Budaya Jawa; Membangun Perilaku Pembungkaman Diri Pada Perempuan Korban Seksual Dalam Kampus - Salma Rabbaniyah; Shafa Salsabila (Jurnal Community, 2022)
The patriarchal culture that is rooted in Indonesia, especially in the Javanese, triggers many problems, especially on relations between genders. Gender inequality in patriarchal culture plays a big role in the occurrence of sexual violence in society, including on campus. There are still many cases of sexual violence on campus that are not reported, one of the reasons is because the victims remain silent. This study aimed to examine the influence of patriarchy in Javanese culture on sexual violence victims on campus who choose to silence themselves. This research uses a qualitative descriptive approach with narrative review method by studying and analyzing literature from various scientific articles that are relevant to the research topic. Strong patriarchal culture in society and the trauma experienced by victims plays a big role in causing them to be reluctant to report what they have experienced and choose to silence themselves. Thus, these findings suggest that self-silencing is carried by victims to maintain interpersonal relationships, avoid conflict, and maintain physical and or psychological safety as a way of protecting oneself in a patriarchal environment.